Engineering Mof/Carbon Nitride Heterojunctions for Effective Dual Photocatalytic co2 Conversion and Oxygen Evolution Reactions - Cardenas-Jiron, G; Granados-Tavera, K (Royal Society of Chemistry, 2024)
Photocatalysis appears as one of the most promising avenues to shift towards sustainable sources of energy, owing to its ability to transform solar light into chemical energy, e.g. production of chemical fuels via oxygen evolution (OER) and CO2 reduction (CO2RR) reactions. Ti metal-organic frameworks (MOFs) and graphitic carbon nitride derivatives, i.e. poly-heptazine imides (PHI) are appealing CO2RR and OER photo-catalysts respectively. Engineering of an innovative Z-scheme heterojunction by assembling a Ti-MOF and PHI offers an unparalleled opportunity to mimick an artificial photosynthesis device for dual CO2RR/OER catalysis. Along this path, understanding of the photophysical processes controlling the MOF/PHI interfacial charge recombination is vital to fine tune the electronic and chemical features of the two components and devise the optimum heterojunction. To address this challenge, we developed a modelling approach integrating force field Molecular Dynamics (MD), Time-Dependent Density Functional Theory (TD-DFT) and Non-Equilibrium Green Function DFT (NEGF-DFT) tools with the aim of systematically exploring the structuring, the opto-electronic and transport properties of MOF/PHI heterojunctions. We revealed that the nature of the MOF/PHI interactions, the interfacial charge transfer directionality and the absorption energy windows of the resulting heterojunctions can be fine tuned by incorporating Cu species in the MOF and/or doping PHI with mono- or divalent cations. Interestingly, we demonstrated that the interfacial charge transfer can be further boosted by engineering MOF/PHI device junctions and application of negative bias. Overall, our generalizable computational methodology unravelled that the performance of CO2RR/OER photoreactors can be optimized by chemical and electronic tuning of the components but also by device design based on reliable structure-property rules, paving the way towards practical exploitation. © 2024 The Royal Society of Chemistry.